An Economic Analysis of Government Revenue and Expenditure in Nepal - Acharya, Krishna Raj (Tribhuvan University Journal, 2017)
The government revenue and expenditure are two key words frequently discussed in economic literature. In the context of Nepal both are increasing but increase in expenditure is rapid than the increase in revenue. Government expenditure if not matched with government income, it may have accompanied with economic evils. Revenue collection if not increased or managed in time, the amount of public debt will increase more rapidly in the future. In this connection, the volume of expenditure is increasing year after year due to the increased role of government in the economy. Revenue mobilization in fiscal year 2012/13 and 2013/14 hovered around 21 percent while that in FY 2014/15 was just 13.8 percent. Contribution of revenue to the total income in FY 2011/12 had remained at 84.85 percent while it grew to 88.65 percent, 89.86 percent and 90.11 percent respectively in the fiscal years from 2012/13 2013/14, and 2014/15 respectively. Hence the volume of public expenditure is increasing rapidly year after year. In FY2012/13 increase in public expenditure was 5.74 percent per annum which reached to 22.18 per annum in year 2014/15.